RIG-I and MDA5 are modulated by bone morphogenetic protein (BMP6) and are essential for restricting Zika virus infection in human Sertoli cells - Jiyarom, Boonyanudh; Giannakopoulos, Stefanos; Strange, Daniel P.; Panova, Nataliya; Gale, Michael; Verma, Saguna (Frontiers in Microbiology, 2023)
Sexual transmission of Zika virus (ZIKV) is associated with virus persistence in the testes and shedding in the seminal fluid for months after recovery. We previously demonstrated that ZIKV can establish long-term replication without causing cytotoxicity in human Sertoli cells (SC), responsible for maintaining the immune privileged compartment of seminiferous tubules. Functional gene expression analyses also predicted activation of multiple virus sensing pathways including TLR3, RIG-I, and MDA5. Here, we elucidated which of the RNA virus sensing receptors play a decisive role in restricting ZIKV replication. We show that both poly I:C and IFN-β treatment induced a robust antiviral state and reduced ZIKV replication significantly, suggesting that virus sensing and antiviral signaling are functional in SC. Silencing of TLR3, 7, and 9 did not affect virus replication kinetics; however, both RIG-I and MDA5 played a synergistic role in inducing an anti-ZIKV response. Further, the impact of SC-specific immunosuppressive pathways that collectively regulate SC function, specifically the TGF-β superfamily members, TGF-β, Activin A, and BMP6, on ZIKV replication was investigated. While ZIKV did not modulate the expression of TGF-β and Activin A, BMP6 signaling was suppressed at later stages of infection. Notably, treatment with BMP6 increased IFN-β, p-IRF3, and p-STAT1 levels, and expression of key interferon-stimulated genes including MDA5, suggesting that BMP6 enhances antiviral response in SC. Collectively, this study further delineates the key role of the RIG-I-like receptors in sensing ZIKV in SC, and reveals a novel role of BMP6 in modulating innate immune and antiviral response in the testes.